Exploring Blended Learning in Higher Education: Different Definitions and Teachers’ Perceptions - Maslihatul Bisriyah (JETLe (Journal of English Language Teaching and Learning), 2020)
The interest in and research on blended learning have increased and developed in the last two decades. This study addresses the topic of blended learning particularly exploring the different definitions of blended learning and the views of teachers on blended learning courses. By locating papers on blended learning using specific databases, this systematic study appraises peer-reviewed articles published between 2000 and 2019. After examining the full papers, 32 studies are then selected as they meet all inclusion criteria and answer the research questions. The findings of this study indicate that blended learning is not a homogenous concept since it means different thing to different people. Besides, teachers in the blended courses experience several challenges, hence constant supports and persistent effort from all the components including the related institution should be given to achieve the potential benefits of this learning mode.Keywords:Blended learning, higher education, teacher perception